Localization of rust resistance genes in old local Russian flaxes by methods of classical genetics - S. N. Kutuzova; E. A. Porokhovinova; N. B. Brutch; A. V. Pavlov (Вавиловский журнал генетики и селекции)
Flax rust, a disease  that  destroyed a significant portion  of the yield before  the creation  of resistant varieties, is currently defeated, but it can cause new outbreaks as identical resistance genes  are used in breeding. Since only one of the allelic genes  can be introduced into a variety, the aim of this work is to identify genes  for resistance to the disease  in lines selected during  the evaluation of old Russian flaxes from the VIR collection. The original accessions  were  added to  the  collection  in 1922, that  is, before  the  release  of breeding varieties,  so  their genes  are of natural  origin. The analysis was performed on an artificial infectious  background by methods of classical genetics,  including the test for allelism. Nine monogenic lines with the original R genes  were crossed to tester  varieties for six loci: K, L, M, N, P, and Q. F2 hybrids in the phase  of cotyledon leaves were inoculated with monopustule clones  of the  fungus,  not  virulent  to any of evaluated genes.  Gene allelism was checked  by the absence of the segregation. It was exactly proven  that  R genes  of the k-716 line from the Pskov kryazh (gc-32) and  the  k-780 accession  from the  Minsk oblast  (gc-33) were located  in the  P locus, the  gene  of the  k-846 line from the Ivanovo-Voznesensk oblast (gc-39) was in the M locus, and the gene of the k-834 line from the Vladimir oblast (gc-38) probably belonged to the K locus. The segregation in the crosses of all testers to the k-630 line from the Simbirsk oblast (gc-25) showed that  its gene  was not allelic to any of the known loci. Probably, there  was a formerly unknown locus. The location of the other genes  failed to be identified due to the linkage between loci N and P and the presence of several resistance genes  in some lines. The gene in gc-9 was in either M or K locus; and the genes  of gc-34, gc-40, and gc-46 were located in P or K. Since all the evaluated genes  were original, the genes of these lines were different alleles of the identified loci.